2015
DOI: 10.1103/physreva.92.032504
|View full text |Cite
|
Sign up to set email alerts
|

Magnetizability of the relativistic hydrogenlike atom in an arbitrary discrete energy eigenstate: Application of the Sturmian expansion of the generalized Dirac-Coulomb Green function

Abstract: The Sturmian expansion of the generalized Dirac-Coulomb Green function [R. Szmytkowski, J. Phys. B 30, 825 (1997); 30, 2747(E) (1997] is exploited to derive a closed-form expression for the magnetizability of the relativistic one-electron atom in an arbitrary discrete state, with a pointlike, spinless and motionless nucleus of charge Ze. The result has the form of a double finite sum involving the generalized hypergeometric functions 3F2 of the unit argument. Our general expression agrees with formulas obtain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…In Ref. [10] we have shown that it remains valid for an arbitrary discrete energy eigenstate. However, the aforementioned article contains only two representational tables with values of the relativistic magnetizabilities for some excited states of selected hydrogenlike ions.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In Ref. [10] we have shown that it remains valid for an arbitrary discrete energy eigenstate. However, the aforementioned article contains only two representational tables with values of the relativistic magnetizabilities for some excited states of selected hydrogenlike ions.…”
Section: Introductionmentioning
confidence: 94%
“…Present calculations have been performed with the current value 137.035 999 139 of the inverse of the fine-structure constant recommended by the Committee on Data for Science and Technology (CODATA) [11], in contrast to those described in Ref. [10], in which we have used α −1 = 137.035 98 95 (CODATA 1986), to be able to compare our results with the previous results of other authors [12]. To show how the change in the value of the fine structure constant affects the value of the magnetizability, additionally, we performed calculations for χ with α −1 = 137.035 999 074, recommended by CODATA 2010 (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basing on the analysis of such kind of expressions as the one in the last equation, carried out by us in the appendix to Ref. [12], particularly, using Eq. (A.11) from that article, one may easily prove that F n κ (1) = −1.…”
Section: Magnetic Shielding Constantmentioning
confidence: 99%
“…In Ref. [13], we have analyzed the magnetic dipole moment induced in the relativistic hydrogenlike atom by a weak, static, uniform magnetic field. Actually, we derived analytically an expression for the magnetizability of the atom in an arbitrary excited state, which allowed us then to find numerical values of this quantity for a few low-lying discrete energy eigenstates [14].…”
Section: Introductionmentioning
confidence: 99%